Medical Services; General History (Vol. 4) - Magpherson, W. G., Maj.-Gen.; Mitchell, T. J., Maj. (London His Majesty's Stationery Office, 1924)
Medical services during the operations on the Gallipoli Pennisula; in Mecadonia; in Mesopotamia and North-West Persia; in East Africa; in the Aden Protectorate, and in North Russia. Ambulance Transport during the war.
Include Tables, Maps, Illustrations, Sketches, Appendix and Index.
Based on Official Documents.
Keywords: Medical Service - Military -- Military - General Medical History -- Medical Services; General History (Vol. 4)